(untitled) (Global Journal of Science Frontier Research, 2023)
Objective The present study has been carried out to investigate the effect of Ramadan fasting on human psychology among family physician working in Diyarbak r Turkey Method In this cross-sectional study the universe of the research is composed of family physicians A questionnaire form included Turkish version of the Depression Anxiety Stress Scale DASS-42 was prepared The study was conducted during the summer of 2017 at the final week of Ramadan 21st - 25th of June SPSS 21 0 statistical package was used in the data analysis Results 209 healthy subjects with no known health problems and w ho w ere n ot i n t he r isk g roups i n t erms o f m ental a nd physical health were included in the statistical evaluation Of the 209 people included in the evaluation 163 said they fasted this month in Ramadan and 46 said they did not fast this month in Ramadan According to the DASS score when fasting people were compared to those who did not fast in Ramadan depression p 0 05 anxiety p 0 05 and stress p 0 05 s cores w ere f ound t o b e l ower i n f asting s ample When compared to those who fasted in Ramadan and those who did not fast depression anxiety and stress prevalence were found to be lower in fasting sample Conclision The current study results demonstrated that fasting in the holy month of Ramadan has been effective in diminishing stress anxiety and depression levels Therefore it is concluded that Ramadan fasting has a protective effect on human psychology